The Effectiveness of Internal Audit in Jamaican Commercial Banks - Delroy Chevers; Devon Lawrence; Arlene Laidlaw; Dane Nicholson (Journal of Accounting and Management Information Systems (JAMIS), 2016)
Banks play a vital role in every economy as they hold the savings of the public, provide a means of payment for goods and services, and finance the development of businesses. The financial sector experienced a meltdown, which some critics argued was the result of inadequate regulatory oversight from regulatory bodies and the auditing function. This highlights the ever-increasing attention which should be placed on internal control systems and the critical role being played by the internal audit function in ensuring that weaknesses are minimized and that exposures to risks are adequately identified and managed. Banks in developing countries and especially those in Jamaica might find it difficult to absorb such failures due to severe resource constraints. As a result, this study seeks to investigate the factors that influence the effectiveness of the internal audit function in Jamaican commercial banks. The study found that the quality of audit investigation, organizational independence, professional proficiencies and management support have a significant impact on internal audit effectiveness. It is imperative that the various stakeholders and policy makers understand the important role internal audit plays in the financial viability and financial health of any financial institution.
Keywords: M41; 650; Commercial banks; internal audit; internal controls; Jamaica